Growth of Tamanu Seedlings (Calophyllum inophyllum L.) in flooding on Several Types of Soil - Fatonah, Siti; Permatasari, Indah; Iriani, Dyah (Bulletin of Scientific Research, 2023)
Tamanau (Calophyllum inophyllum L.), has economic value as a source of biofuel and medicine, therefore it has the potential to be developed in several wetlands in Riau, Indonesia. This study aims to examine the growth ability and morphological adaptation of tamanu to flooding conditions on mineral soil, peat soil and sand soil. This experimental research was designed using a randomized block design. The experiment consisted of flooded and non-flooded treatments on mineral soils, peat soils and sandy soils. Flooding was carried out on all types of soil with an inundation level of 2 cm above the soil surface for 30 days. The results showed that Tamanu seedlings are tolerant to flooding on mineral soils and sandy soils, but sensitive to flooding on peat soils. The morphological adaptation of tamanu seedlings to flooding in mineral soils is the formation of adventitious roots and lenticels. Tamanu seedlings when submerged in sandy soil only form pores on submerged stems.